2017
DOI: 10.1634/theoncologist.2016-0213
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Psychosocial Barriers to and Benefits of Cervical Cancer Screening in Kenya

Abstract: Background. Cervical cancer is the second most commonly diagnosed cancer in females and is a leading cause of cancerrelated mortality in Kenya; limited cervical cancer screening services may be a factor. Few studies have examined men's and women's perceptions on environmental and psychosocial barriers and benefits related to screening. Materials and Methods. In 2014, 60 women aged 25-49 years and 40 male partners participated in 10 focus groups (6 female and 4 male), in both rural and urban settings (Nairobi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 11 publications
4
48
1
1
Order By: Relevance
“…Previous studies have reported concerns of marital discord occurring after a woman informs her husband that she has cervical cancer [9,11]. We uniquely found that male and female participants' concerns about the need to abstain from sexual intercourse while a woman is undergoing treatment, doctors not discussing the treatment process with husbands, and women's fear of marital discord can negatively impact their decision to seek treatment.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous studies have reported concerns of marital discord occurring after a woman informs her husband that she has cervical cancer [9,11]. We uniquely found that male and female participants' concerns about the need to abstain from sexual intercourse while a woman is undergoing treatment, doctors not discussing the treatment process with husbands, and women's fear of marital discord can negatively impact their decision to seek treatment.…”
Section: Discussionmentioning
confidence: 73%
“…Several treatment barriers identified in this study are similar to barriers associated with cervical cancer screening, such as knowledge gaps, religious or cultural beliefs, spousal approval, stigma, and access to services [9]. Although the NCCPP Strategic Plan promotes see-and-treat approaches for precancerous lesions and treatment of diagnosed cervical cancer, the majority of screening clinics lack treatment services [4].…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that several barriers exist to accessing healthcare services in LMICs, such as distance to nearest health facility, lack of resources, and complex bureaucratic referral systems [22]. These barriers are linked to poor health outcomes [22][23][24]. Therefore, if access to healthcare services for basic treatment is limited, and health outcomes remain poor as a result, the common notion is that it is unlikely and even unwise to focus efforts towards less ''urgent'' initiatives, like patient involvement in research.…”
Section: Gaps In Health Infrastructurementioning
confidence: 99%
“…In many settings, the diagnosis of an illness can lead to unpleasant effects on community life, such as social isolation and stigmatization [24,25,32]. Patients with cancer report experiencing social stigma, with consequences such as termination of employment, familial shame, and social rejection [23,31,33].…”
Section: Cultural Stigmamentioning
confidence: 99%
See 1 more Smart Citation